Collaborative Governance in Basic Education Services in Indonesia-Malaysia Border Area - Mawar Mawar; Abdul Rahman; Retnowati Wahyuning Dyas Tuti; Nida Handayani; Muhammad Sahrul; Dini Gandini Purbaningrum (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
This study examines the implementation of collaborative governance in essential education services in Indonesia-Malaysia's border area, in Entikong-Sekayam District, Sanggau Regency, West Kalimantan Province. It used a descriptive technique with a qualitative approach, with data collected through observation, interviews, and documentation. The data was analyzed with qualitative techniques and tested for validity by triangulation. According to the results, collaborative governance had not yet achieved desired results. This was based on several indicators, including starting conditions, facilitative leadership, institutional design, and collaborative processes. Importantly, the collaborative process involved several parties, including the government through the Ministry of Education and Culture, and the Ministry of Public Works and Housing, academics at the Faculty of Social and Political Sciences of Jakarta Muhammadiyah University, and elementary school figures (school committees, principals, staff and teachers). The results showed that the government’s role was not maximized, as indicated by uncertain policies and systems, overlapping authority, and inappropriate school infrastructure assistance targets. Academics actively facilitate various activities, including socialization, mentoring, workshops, and training, significantly improving education quality. Schools also operate an intense performance in mobilizing teachers to remain active amid the limitations of existing facilities and increasing their competence. Moreover, school committees also contribute ideas, energy, and materials in development, especially physical facilities. The weakness of the collaboration process in essential education services is the absence of private sector involvement.